Reduced tongue tone associated with degeneration of the hypoglossal nerve nucleus in a horse with equine motor neuron disease. (3rd November 2013) - Robin, M.; Malbon, A.; Ricci, E.; McGowan, C.; Malalana, F.
Summary: Equine motor neuron disease (EMND) is a condition characterised by generalised weakness and muscle atrophy associated with degeneration of motor neurons in the ventral horns of the spinal cord. Despite the frequent detection of cranial nerve nuclei pathology during post mortem examination, associated clinical signs are rarely reported. This report describes a case of EMND in a pony gelding that presented with clinical signs of diffuse neuromuscular weakness associated with marked flaccidity of the tongue, making differentiation from similar neuromuscular conditions, particularly botulism, extremely challenging.